Effect of crizanlizumab on pain crises in subgroups of patients with sickle cell disease: A SUSTAIN study analysis. Issue 1 (25th November 2018) - Kutlar, Abdullah; Kanter, Julie; Liles, Darla K.; Alvarez, Ofelia A.; Cançado, Rodolfo D.; Friedrisch, João R.; Knight‐Madden, Jennifer M.; Bruederle, Andreas; Shi, Michael; Zhu, Zewen; Ataga, Kenneth I.
Abstract: The cell adhesion molecule P‐selectin plays a key role in the pathogenesis of a vaso‐occlusive crisis (VOC) in patients with sickle cell disease (SCD). In the double‐blind, placebo‐controlled phase 2 SUSTAIN study, crizanlizumab (humanized, anti‐P‐selectin monoclonal antibody) 5 mg/kg significantly lowered the rate of VOC in patients with SCD by 45% vs placebo. In SUSTAIN, patients with SCD were randomized to crizanlizumab 2.5 mg/kg, crizanlizumab 5 mg/kg, or placebo intravenously 14 times over 52 weeks. The primary endpoint was the annual rate of VOC with crizanlizumab vs placebo. This post hoc descriptive analysis evaluated the proportion of patients who did not experience a VOC during the study in the following subgroups: VOCs in the year prior to study entry (2‐4/5‐10), SCD genotype (HbSS/non‐HbSS), and concomitant hydroxyurea use (yes/no). More patients were VOC event‐free in the crizanlizumab 5 mg/kg arm than in the placebo arm, including those with more frequent prior VOCs (ie, 5‐10; 28.0% vs 4.2%), the HbSS genotype (31.9% vs 17.0%) and/or using concomitant hydroxyurea (33.3% vs 17.5%). Further analyses of secondary endpoints demonstrated that crizanlizumab treatment significantly increased time‐to‐first VOC vs placebo in these subgroups. The rates of treatment‐emergent adverse events were similar between treatment arms across all subgroups. This post hoc analysis of SUSTAIN shows that in patients with a high number of prior VOCs, on concomitant hydroxyurea and/or with the HbSS genotype, crizanlizumab treatment increases the likelihood of patients being VOC event‐free and delays time‐to‐first VOC.